Identifying Barriers to the Implementation of the Standard Inpatient Class (KRIS): A Study in Denpasar City's Private Hospitals - Effendi, Julham; Manuaba, I.B.G. Fajar; Sanjaya, I.N Hariyasa; Tania Fidzikri, Nanda Berliana; Yamin, Imam Syahputra (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: The Indonesian government and BPJS Kesehatan plan to replace the current class-based inpatient system with a Standard Inpatient Class (KRIS) to ensure service equality. Government Regulation No. 47 of 2021 mandates that private hospitals must prepare at least 40% of their beds for KRIS. A preliminary survey showed only 57% of private hospitals in Denpasar were ready for this implementation. Objective: This study aimed to identify and analyze the obstacle factors in the implementation of KRIS in private hospitals in Denpasar. Method: This study used a qualitative design with a descriptive approach. Data were collected through in-depth interviews with 17 informants, including representatives from 14 private hospitals, BPJS Kesehatan, and the Provincial and City Health Offices between April and July 2023. Data were analyzed using thematic analysis. Result and Discussion: The study identified four main barriers: 1) Resource factors, particularly in meeting 12 KRIS criteria such as room density (50% compliance), bathroom accessibility (57.14%), and oxygen outlets (71.42%), compounded by land, building, and budget limitations; 2) Communication issues, including differing perceptions of KRIS implementation regulations; 3) Disposition challenges, where hospitals feel unable to meet the implementation timeline and 4) Bureaucratic hurdles, specifically the absence of specific technical government regulations. Conclusions: The most dominant obstacles are inadequate facilities and infrastructure, land and budget constraints, differing information perceptions, unachievable implementation targets, and the lack of technical guidelines.